Placebo Effect on Modulating Empathic Pain: Reduced Activation in Posterior Insula - Zhao, Yili; Liu, Ruixuan; Zhang, Jianxin; Luo, Jing; Zhang, Wencai (Frontiers in Behavioral Neuroscience, 2020)
Little evidence exists to confirm whether the sensory-related neural activity that occurs when observing others in pain is highly responsive to empathy for pain. From a perspective of intervention, the present study employed placebo manipulation with a transferable paradigm to explore whether the sensory regional activation that occurs when viewing pictures of others in pain could be modulated by placebo effect. We first performed a screening behavioural experiment for selecting placebo responders and then entered them into a functional magnetic resonance experiment in which they were exposed to the same conditions as before. Participants were informed that it was equally possible to be assigned to the treatment group (placebo manipulation) or the no treatment group (control); they all in fact received treatment and placebo effect would be detected by comparing placebo condition and no-placebo control condition. Each participant experienced a phase of reinforcing placebo belief with pain in self and a phase of testing transferable placebo effect on empathy for pain. As a result, we found significant activation in sensory areas, including the posterior insula and the postcentral gyrus, and in the middle cingulate cortex while participants observed pictures of others in pain. More importantly, for the first time, we observed relived activation in the posterior insula modulated by placebo effect only associated with pain pictures but not with no-pain pictures. This suggests that sensory activity in the posterior insula might be involved in the processing for empathic pain. This new approach sheds light on research and applications in clinical settings.